Population dynamics and life tables of the mango mealbug, Rastrococcus invadens Williams, and its introduced natural enemy Gyranusoidea tebygi Noyes in Benin - Boavida, C.; Neuenschwander, Peter (Informa UK Limited, 1995)
Life table data for Rastrococcus invadens and its introduced natural enemy Gyranusoidea tebygi were obtained in the field and in the laboratory. The mealybug population's potential rate of increase ranged from 0.066/day to 0.078/day. The potential for increase of the parasitoid was double that of its host. Seasonal fluctuations in abundance of R. invadens were followed from 1988 to 1992 on mango trees in southern Benin. The population density of R. invadens decreased during the rainy seasons and peaked during the dry seasons. Mealybug field sex ratios were extremely variable, and the impact of such variability on the mealybug's potential rate of increase was analyzed. The populations of the exotic encyrtid G. tebygi, introduced into Benin in 1988 for control of the pest, were synchronized with the host populations. The spatial patterns of parasitism distribution in relation to the host population density were either independent or directly density-dependent, both at the tree level and for larger zones. However, reducing the scale of analysis resulted in different types of relationships. The impact of predators was a minor factor in the population dynamics of the mealybug. Four of the six species of hyper-parasitoids attacking mealybugs parasitized by G. tebygi developed high populations. In the two orchards studied, mealybug populations eventually collapsed and disappeared. This fact is discussed as being an indication that the biological control of the mango mealybug by G. tebygi was achieved by non-equilibrium local dynamics, and should be evaluated in a meta-population perspective.